Pendampingan Penerapan Model Pembelajaran Kecerdasan Majemuk bagi Guru di SMA 16 Bone - Akmal Hamsa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Teachers are required to have the ability to use various methods or combine several relevant methods so that they are able to integrate the development of students' multi-intelligences in the learning process. Based on the results of observations, information was obtained from the school that they experienced several problems in the teaching and learning process, namely that teachers in the classroom learning process were still classical, teachers had never received training in multiple intelligences learning models, while on the other hand students were required to be creative in developing knowledge in the learning process. This assistance is intended to improve teachers' abilities in implementing effective learning models by implementing multiple intelligence learning models which can be used as fun learning models in the classroom. This assistance aims to provide understanding to high school teachers about effective learning by implementing the multiple intelligence learning model, increasing the ability of high school teachers in planning, implementing and evaluating using the multiple intelligence learning model, implementing this learning model in high school according to the conditions and potential of students. The methods used include lecture, question and answer, discussion, practice and assignment methods.